Identification of a cell‐wall peptidase (NlpC/P60) from Nocardia seriolae which induces apoptosis in fathead minnow cells. Issue 5 (20th March 2020) - Hou, Suying; Chen, Guoquan; Wang, Wenji; Xia, Liqun; Wang, Zhiwen; Lu, Yishan
Abstract: Nocardia seriolae, a Gram‐positive bacterium, is the main pathogen of fish nocardiosis. Protein NlpC/P60 is a cell‐wall peptidase and a potential virulence factor of N. seriolae . Subcellular localization research revealed that both NlpC/P60‐GFP and NlpC/P60Δsig‐GFP fusion proteins were evenly distributed in the whole cell of fathead minnow (FHM) cells. Furthermore, typical apoptotic features, such as nuclear pyrosis and apoptotic bodies, were observed in the transfected FHM cells and grouper spleen cells by the overexpression of protein NlpC/P60. Then, quantitative assays of mitochondrial membrane potential (ΔΨm) value, caspase‐3 activity and apoptosis‐related gene ( Bax, BNIP3, TNF1 and TNF6 ) mRNA expression were conducted. The results showed that ΔΨm was decreased, caspase‐3 was significantly activated, and the mRNA expression of pro‐apoptotic genes ( Bax and BNIP3 ) and tumour necrosis factors ( TNF1 and TNF6 ) was up‐regulated in NlpC/P60 ‐overexpressed cells. Taken together, the results indicated that the protein NlpC/P60 of N. seriolae might involve in apoptosis regulation. This study may lay the foundation for further study on the function of N. seriolae NlpC/P60 and promote the understanding of the virulence factors and pathogenic mechanism of N. seriolae .